THE EFFECT OF CAPITAL EXPENDITURE ON DOMESTIC INVESTMENT AND FOREIGN INVESTMENT WITH INFLATION AS A MODERTTING VARIABLE - Nico Hutabarat, Frans; Lenggogeni (Universitas Tidar, 2022)
This research aimed to know how the effect of capital expenditure and inflation variable to the Domestic and Foreign Investment in Indonesia especially Provinces in Java Island in 2016 to 2020. This research used the panel data regression method with time-series data from the Central Bureau of Statistics (BPS) and the Directorate General of Fiscal Balance’s portal data. The results of this study are the inflation variable partially significant effect on Foreign Investment in provinces in Java Island. On the contrary, the capital expenditure variable does not have a significant effect both on domestic and foreign investment, while the inflation variable strengthens the relationship between capital expenditures and domestic investment. Keywords : Capital Expenditure, Domestic Investment, Foreign Investment, Inflation